Menelisik Randai sebagai Teater Tradisional dan Identitas Budaya Minangkabau di Muaro Takung - Nevi Riviony; Adinda Fitraini; Ilham Alzikri; Monalisa Agnes Permata; Rachma Alya Gunawan; Randi Purnama Putra (Lembaga Yasin AlSys, 2026)
Although Randai, as a traditional Minangkabau theater, has received attention in several previous studies, research that specifically discusses Randai as a cultural identity in Muaro Takung remains limited. This study aims to explore the role of Randai in strengthening Minangkabau cultural identity in Muaro Takung. This study employed a qualitative approach with an ethnographic design, involving 20 Randai studio participants selected through purposive sampling. Data were collected through participatory observation, interviews, and document analysis, and were then analyzed thematically. The findings show that Randai is integrated into traditional rituals, such as birth, marriage, and death, without depending on a formal stage. Randai practice combines elements of silat, dance, music, and gurindam based on the values of adat basandi syarak. These findings indicate that Randai functions not only as a form of folk performing art but also as a medium for value transmission, the strengthening of social solidarity, and the affirmation of Minangkabau cultural identity. The conclusion of this study emphasizes the importance of preserving Randai studios by the younger generation as a strategy for maintaining the sustainability of local culture amid the currents of globalization. The implications of this study provide a theoretical contribution to the development of studies on folk performing arts and the cultural resilience of rantau, as well as practical implications for the integration of Randai into cultural education and the development of Sijunjung tourism. This study also opens opportunities for further research on the Randai diaspora in the broader context of Minangkabau society.